2011
DOI: 10.1016/j.bbr.2011.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory conditioning to the interoceptive nicotine stimulus blocks subsequent conditioning to an exteroceptive light stimulus

Abstract: Previous research has shown that a nicotine conditional stimulus (CS) can compete with (i.e., overshadow) a brief light CS. Another form of competition, blocking, has not yet been examined with the nicotine CS. Groups of rats were assigned to an element training condition. For the N+ group, during each daily 2-hr element training session, there were ten intravenous nicotine infusions (0.03 mg/kg) followed 30-sec later with 4-s access to sucrose. In the N- group, nicotine and sucrose presentations were explicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Nicotine has been shown to serve as a discriminative stimulus (Palmatier & Bevins 2008). Furthermore, Bevins and colleagues have demonstrated a role for nicotine as a CS+ or CS- itself (Murray & Bevins 2007; Murray et al 2011), and that the interoceptive stimulus effects of nicotine can even overshadow a light stimulus in gaining control of conditioned responding for sucrose (Murray & Bevins 2011). Clearly, nicotine has a powerful ability to serve as an informative cue.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine has been shown to serve as a discriminative stimulus (Palmatier & Bevins 2008). Furthermore, Bevins and colleagues have demonstrated a role for nicotine as a CS+ or CS- itself (Murray & Bevins 2007; Murray et al 2011), and that the interoceptive stimulus effects of nicotine can even overshadow a light stimulus in gaining control of conditioned responding for sucrose (Murray & Bevins 2011). Clearly, nicotine has a powerful ability to serve as an informative cue.…”
Section: Discussionmentioning
confidence: 99%
“…The list of internal stimuli is extensive and includes thoughts, anxiety, pain, hunger, satiety, stress, intoxication, and so forth Learning that modifies behavioral and physiological processes controlled by internal stimuli has been implicated in such health issues as cancer treatment, cardiovascular disease, obesity, mental health disorders, and drug addiction (Ceunen, Vlaeyen, & Van Diest, 2016; Davidson, 1993; Fadel & Burk, 2010; Koroboki et al, 2010; Meagher, 2010; Murray & Bevins, 2011; Oldershaw et al, 2011; Paulus & Stein, 2010; Wylie & Tregellas, 2010). Of particular relevance here is the research on how learning processes modify the behavior controlled by drug stimuli (Bevins & Besheer, 2014).…”
mentioning
confidence: 99%
“…Goal-tracking refers to approach behavior to a location where the reinforcer has occurred in the past (Boakes, 1977; Farwell and Ayres, 1979). Previous research has shown that this acquired appetitive behavior controlled by the nicotine stimulus does not reflect state-dependent learning (Bevins et al, 2007; Murray and Bevins, 2011), cannot be attributed to a non-associative or stimulant effect of nicotine (Besheer et al, 2004; Murray et al, 2009; Reichel et al, 2007; Wilkinson et al, 2006), and follows many postulates of Pavlovian conditioning (Bevins and Murray, 2011; Murray et al, 2009). …”
Section: Introductionmentioning
confidence: 89%
“…This drug stimulus can acquire control over behavior (Murray and Bevins, 2011). In the laboratory, human participants will learn to discriminate nicotine from saline and place poker chips in a particular pile when under the influence of nicotine (Perkins et al, 1999).…”
Section: Introductionmentioning
confidence: 99%